2020
DOI: 10.1038/s41598-020-70199-4
|View full text |Cite
|
Sign up to set email alerts
|

Utilitarianism in minimal-group decision making is less common than equality-based morality, mostly harm-oriented, and rarely impartial

Abstract: In the study of utilitarian morality, the sacrificial dilemma paradigm has been the dominant approach for years. However, to address some of the most pressing issues in the current research literature, the present studies adopt an alternative approach by using a minimal group paradigm in which participants have to make decisions about the allocation of resources. This approach allows not only to pit utilitarianism against equality-based morality, but also to study these modes of morality for both harm and bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…However, one possible explanation for the increased proportion of switch decisions uncovered in the current study might be that participants were asked to make sacrificial moral judgments that were framed in terms of benefits rather than harms. Prior research by Roets et al (2020) has established that participants tend to be more fairnessminded when they are asked to distribute benefits, and more utilitarian when asked to make decisions on distribution tasks involving harms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one possible explanation for the increased proportion of switch decisions uncovered in the current study might be that participants were asked to make sacrificial moral judgments that were framed in terms of benefits rather than harms. Prior research by Roets et al (2020) has established that participants tend to be more fairnessminded when they are asked to distribute benefits, and more utilitarian when asked to make decisions on distribution tasks involving harms.…”
Section: Discussionmentioning
confidence: 99%
“…When a dilemma is repeated, we are not just limited to either refraining from harm or minimizing overall harm, we also have the option to spread harm across all targets. Prior research has already demonstrated that fairness considerations can sometimes trump utilitarian concerns (Roets et al, 2020). By constraining the study of sacrificial harm to research paradigms involving oneshot judgments of mortal harm dilemmas, moral psychologists have ignored the contextualized nature of moral decision making, and have removed this additional moral concern from the equation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, prior research has already demonstrated that fairness considerations can trump utilitarian concerns (Roets et al, 2020). By constraining the study of sacrificial harm to research paradigms involving one-shot judgments of mortal harm dilemmas, moral psychologists have ignored the contextualized nature of moral decision making and removed this third moral concern from the equation.…”
Section: Introductionmentioning
confidence: 99%
“…E.g.,Brandt and Sleegers 2021;De Cruz 2020;Funkhouser 2020;Oyserman and Dawson 2019;Roets et al 2020;Strohminger 2018;Van Bavel and Pereira 2018. …”
mentioning
confidence: 99%